PELAKSANAAN HUKUM KEWARISAN ISLAM PADA MASYARAKAT DUSUN PLOSO KUNING DI KABUPATEN SLEMAN - , Nanang Bagus Panuntun ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is aimed to understand and study implementation of inheritance process at Ploso Kuning village of Sleman Regency, effect of Islamic inheritance law on implementation of inheritance at Ploso Kuning village of Sleman Regency. This is empirical law research that emphasized field data as main data source. To support and complete data, library research was done by literary study to obtain secondary data. The data was analyzed with descriptive qualitative method. Research subject was determined using non random sampling technique with purposive sampling in which sample was taken by determining certain terms that should be met. The research used 50 respondents and three informants. Based on the researchâs result, obtained a conclusion as well as answering the problem defitinion adopted by the author that heritage law applied in Ploso Kuningâs Villagers still using Islamic Heritage Law, even if the implementation still not appropriate with the Faraidl rate and the settlement of heritage division get done by discussion. Obstacles in its implementation included low education and knowledge level on inheritance law, effect of economic level, effect of other inheritance law, insufficient dissemination on Islamic inheritance law compilation.